Measuring the impact of dermatological conditions on family and caregivers: a review of dermatology‐specific instruments. (19th May 2017) - Sampogna, F.; Finlay, A.Y.; Salek, S.S.; Chernyshov, P.; Dalgard, F.J.; Evers, A.W.M.; Linder, D.; Manolache, L.; Marron, S.E.; Poot, F.; Spillekom‐van Koulil, S.; Svensson, Å.; et al.
Abstract: The patient is the centre of a web of relationships, and the impact of his/her disease on family members and caregivers must be taken into account. The aim of this study was to identify the specific instruments that measure the impact of a dermatological disease on the quality of life (QoL) of family members, by performing a systematic search of the literature. Fifteen papers were identified, describing the creation and validation of nine instruments. Four of them concerned atopic dermatitis (Dermatitis Family Index, DFI; Parents' Index QoL Atopic Dermatitis, PiQoL‐AD; QoL in primary caregivers of children with atopic dermatitis, QPCAD; Childhood Atopic Dermatitis Impact Scale, CADIS), two measured the impact of psoriasis in family members (Psoriasis Family Index, PFI; FamilyPso), one the impact of epidermolysis bullosa (Epidermolysis Bullosa Burden of Disease, EB‐BoD), one of ichthyosis (Family Burden Ichthyosis, FBI), and one was generic for dermatological conditions (Family Dermatology Life Quality Index, FDLQI). The European Academy of Dermatology and Venereology quality of life taskforce recommends that the impact of a skin disease on family and caregivers should be measured as part of any thorough evaluation of the burden of a disease. Guidelines are given to choose the most appropriate instruments.